A highly sensitive resonance Rayleigh scattering and colorimetric assay for the recognition of propranolol in β‐adrenergic blocker. (19th May 2017) - Tan, Xuanping; Yang, Jidong; Yang, Qiong; Li, Qin
Abstract: In this work, a highly sensitive, citrate anion‐capped gold nanoparticles (AuNPs)‐based assay for the determination of propranolol in real samples with resonance Rayleigh scattering (RRS) and colorimetry was developed. When AuNPs were prepared by the sodium citrate reduction method, citrate anions self‐assembled on the surface of AuNPs to form supramolecular complex anions. In BR 4.6 buffer solution, propranolol was positively charged and could bind with AuNPs to form larger aggregates through electrostatic force and hydrophobic effects. This results in remarkable enhancement of the RRS intensity and a color change in the AuNPs solution from red to blue via purple. Thus, a highly sensitive RRS and colorimetric assay the for detection of propranolol was developed with a linear range of 0.2–5.2 and 8–112 ng/ml, respectively. In addition, no difference was seen when comparing R ‐propranolol with S ‐propranolol, therefore, this method could not be used in the recognition of chiral propranolol. However, upon addition of other β‐adrenergic blockers, no phenomenon like that seen with propranolol was observed, meaning that this method can be used for determining the presence of propranolol in a mixture β‐adrenergic blockers. Finally, the optimum conditions, factors influencing the reaction, its mechanism and the reasons for enhancement of the RRS were discussed.